USP25 Regulates the Proliferation and Apoptosis of Ovarian Granulosa Cells in Polycystic Ovary Syndrome by Modulating the PI3K/AKT Pathway via Deubiquitinating PTEN - Gao, Yue; Chen, Jiao; Ji, Rui; Ding, Jinli; Zhang, Yan; Yang, Jing (Frontiers in Cell and Developmental Biology, 2021)
Background: Polycystic ovarian syndrome (PCOS) is an endocrine-related disease related to abnormal folliculogenesis and is a leading cause of infertility worldwide. Inhibition of granulosa cells (GCs) proliferation and increased GCs apoptosis have been identified as the major factors in aberrant follicle maturation. Methods: USP25 and PTEN expression in GCs from women with and without PCOS was analyzed using Western blotting. A PCOS-like mouse model was constructed using USP25 knockout and wild-type mice to explore the role of USP25 in PCOS. The human granular cell line KGN was cultured for proliferation and apoptosis assays, and the effect of USP25 on PTEN was investigated after transfection with shRNA-USP25 lentivirus. Results: USP25 expression was found to be elevated in patients and mice with PCOS. With mouse model, we observed a reduction in PCOS symptoms in mice after USP25 deletion. Increased proliferation, reduced apoptosis, activation of the phosphoinositide-3-kinase (PI3K)/protein kinase B (AKT) signaling pathway and decreased PTEN expression were found in KGN cells after USP25 knockdown. Finally, we verified that USP25 could deubiquitinate PTEN in KGN cells. Conclusions: In this study, we investigated that USP25 can regulate the PI3K/AKT signaling pathway by deubiquitinating PTEN, thus affecting the proliferation and apoptosis of GCs and contributing to the pathogenesis of PCOS.